The influence of dynamic capabilities on the inclusion of stakeholders in the responsible innovation process: the case of healthcare technology companies - Silva, Luciana Maines da (Universidade do Vale do Rio dos Sinos, 2020)
The traditional development of innovation often generates unknown impacts. The search for responsible innovation establishes the management of (external) stakeholders' interests as a way to minimize uncertainty and maintain or develop a competitive advantage. Also, there is a concern with ethical, social, and environmental aspects. The inclusion of stakeholders during the responsible innovation process enables the integration of new and significant knowledge. For inclusion to be leverage, dynamic capabilities are required. This thesis analyzed how dynamic capabilities leverage the inclusion of stakeholders in the innovation process. Two equipment developer companies from the healthcare sector, recognized worldwide, were analyzed. The sector was chosen by the potential to provide high-quality solutions that offer better results and reliability, improving productivity and service to patients. The analysis of the cases pointed to specific processes and routines for the inclusion of stakeholders, which constitutes the microfoundations of dynamic capabilities. The particular processes and routines are cocreation, memory creation, strategic partnerships, active participation in events, systematic observation of product use, encouraging training and qualification of users, and the establishment of multiple communication channels. From the microfoundations, generic and specific dynamic capabilities were identified, which leverage the inclusion. The comparative analysis of the cases pointed to four propositions: (1) The inclusion of stakeholders occurs throughout the responsible innovation process, favored by the Stage-gate model; (2) the inclusion of stakeholders in the responsible innovation process requires particular processes and routines; (3) the generic dynamic capabilities of sensing, seizing and transforming, and the specific dynamic capabilities, relational and Integrative knowledge, based on particular processes and routines, leverage the inclusion of stakeholders in the process of responsible innovation; and (4) specific dynamic capabilities contribute to greater responsible innovation maturity. Theoretical contributions stand out as the approximation of the theoretical lens of dynamic capabilities to the context of responsible innovation. Specifically, about dynamic capabilities, the possibility of operationalization is demonstrated, from its microfoundations. The concept of generic dynamic capabilities is developed – which leverage various processes, and specific dynamic capabilities – that leverage a given process. Empirical advances are mainly due to detailing the inclusion process, considered to be one of the governance aspects of responsible innovation. Another increase is to demonstrate to entrepreneurs and managers the case of global companies in the healthcare sector, recognized for responsibility in innovation. A responsible innovation governance model was also developed, inspired by the Canvas model, which contributes to companies evaluating and seeking responsible innovation development.
Keywords: Responsible innovation; Dynamic capabilities; Stakeholder; Inclusion; Healthcare; Inovação responsável; Capacidades dinâmicas; Inclusão; Saúde; ACCNPQ::Ciências Sociais Aplicadas::Administração